Pengukuran dan Pelatihan Kesiapsiagaan Komunitas Sekolah Dasar Muhammadiyah Banyuraden terhadap Bencana Gempa Bumi - Restu Faizah; Seplika Yadi; Muhammad Ibnu Syamsi; Retnowati Setioningsih (Journal of Dedicators Community, 2021)
The earthquake that occurred during school hours requires the school community to have a high level of preparedness so as not to fall victim and loss a lot. This activity aims to measure the level of preparedness against the threat of earthquake disasters and provide earthquake disaster preparedness training to the Muhammadiyah Banyuraden Elementary School community. The method used was a survey using a questionnaire, analysis of survey results based on the UNSESCO framework, namely knowledge of earthquake disasters, policies and guidelines, emergency response plans, and resource mobilization. The analysis showed that the community preparedness level of SD Muhammadiyah Banyuraden was at a moderate level with a total preparedness index of 55.8. The lowest preparedness index is in the policy and guideline parameters. The results of the survey and analysis carried out resulted in preparedness strengthening activities carried out to increase the preparedness index, namely the formation of disaster preparedness groups, compiling evacuation route maps, adapting earthquake simulations, training on first aid and evacuation, and simulating earthquake evacuation. The activities to strengthen preparedness have an impact on the preparedness index